2020
DOI: 10.3233/prm-190614
|View full text |Cite
|
Sign up to set email alerts
|

Lessons learned from conducting a pragmatic, randomized, crossover trial on robot-assisted gait training in children with cerebral palsy (PeLoGAIT)

Abstract: PURPOSE: To investigate the effectiveness of outpatient robot-assisted gait training (RAGT) in ambulatory children with spastic cerebral palsy. METHODS: Children were randomized to two different intervention sequences within a pragmatic crossover design. They performed five weeks of RAGT (3 sessions per week) and five weeks of usual care (UC). Dimension E of the Gross Motor Function Measure-88 (GMFM E) as the primary outcome as well as Dimension D (GMFM D), and timed walking tests were assessed before and afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 53 publications
0
26
0
Order By: Relevance
“…The overall effect was not significantly different between the robotic gait training and control intervention for both Gross Motor Function Measure-D (95% CI: −0.29, 0.39; P = 0.77; Figure 4) and -E (95% CI: −0.11, 0.57; P = 0.19; Figure 5). Four of the five studies 18,19,21,22 evaluating Gross Motor Function Measures-D and -E used a Lokomat device, and a Lokomat-specific pooled effect on these measures was also not significantly different from the control interventions tested (GMFM-D 95% CI: −0.25, 0.49; P = 0.52; GMFM-E 95% CI: −0.10, 0.65; P = 0.15; Appendix B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall effect was not significantly different between the robotic gait training and control intervention for both Gross Motor Function Measure-D (95% CI: −0.29, 0.39; P = 0.77; Figure 4) and -E (95% CI: −0.11, 0.57; P = 0.19; Figure 5). Four of the five studies 18,19,21,22 evaluating Gross Motor Function Measures-D and -E used a Lokomat device, and a Lokomat-specific pooled effect on these measures was also not significantly different from the control interventions tested (GMFM-D 95% CI: −0.25, 0.49; P = 0.52; GMFM-E 95% CI: −0.10, 0.65; P = 0.15; Appendix B).…”
Section: Resultsmentioning
confidence: 99%
“…Five studies, [17][18][19]21,22 with no significant heterogeneity (Gross Motor Function Measure-D: P = 0.76, I 2 = 0%; Gross Motor Function Measure-E: P = 0.83, I 2 = 0%) and comprising 65 robotic gait training participants and 70 control participants, assessed changes in Gross Motor Function Measure-D and -E scores. The overall effect was not significantly different between the robotic gait training and control intervention for both Gross Motor Function Measure-D (95% CI: −0.29, 0.39; P = 0.77; Figure 4) and -E (95% CI: −0.11, 0.57; P = 0.19; Figure 5).…”
Section: Resultsmentioning
confidence: 99%
“…Amman-Reiffer et al ( 25 ) found no significant difference in ROM between using conventional physiotherapy and RAGT therapy in children with CP. In this work, an improvement in ROM was observed between the initial session and the end of the study.…”
Section: Discussionmentioning
confidence: 98%
“…The results from a second study by the same authors also showed improved dynamic balance during walking in children and adolescents with CP following Lokomat training [33]. Finally, only five of these studies [30,[32][33][34][35] were completed in a randomized controlled process, and only three of these studies [23,24,28] provided a short-term follow-up of the observed changes. Moreover, the methodological quality of the included studies ranged from 2 to 7 out of 10, with a median score of 3 (Table 2).…”
Section: Evidence Of the Effectiveness Of Robotic Gait Training In Ch...mentioning
confidence: 99%
“…Moreover, the methodological quality of the included studies ranged from 2 to 7 out of 10, with a median score of 3 (Table 2). Only 5/13 studies [31,[33][34][35][36] were of a good quality (PEDro score ≥ 6). Thus, despite the generally positive effects reported in some of the studies, no consensus has been reached regarding the effectiveness of Lokomat training.…”
Section: Evidence Of the Effectiveness Of Robotic Gait Training In Ch...mentioning
confidence: 99%